COMPASS: A New COnductance Model Based on PFISR And SWARM Satellite Observations - Zihan Wang; Shasha Zou (Space Weather)
Abstract Ionospheric conductance plays a crucial and active role in magnetosphere‐ionosphere‐thermosphere coupling processes. Despite its importance, direct global observations of conductance are unavailable. This limitation inspires the development of empirical models that are widely used to specify global distributions of conductance indirectly. In this work, a new model, COnductance Model based on PFISR And SWARM Satellite observations, describing the statistical relationships between conductance and field‐aligned currents (FACs) is presented. The conductance was calculated using the electron densities measured by Poker Flat Incoherent Scattering Radar (PFISR), and the FACs were determined by the magnetic perturbations measured by SWARM at Low‐Earth Orbit. Between 2014 and 2020, there were ∼3,900 conjunction events between PFISR and SWARM, providing a large data set for investigating the relationship between conductance and FACs. It is found that both Hall and Pedersen conductances vary as a power of j∥, and the power index a depends on magnetic local time and the direction of FACs, ranging from 0.0 to 0.6. Properties of this power index a are founded as follows: (a) the largest power index is obtained on the dawn side, and the minimum is at noon; and (b) the power indices are positive for both upward and downward FACs and are larger for upward FACs than downward FACs. The underlying physical mechanisms of the observed variations of the model parameters are also discussed. Despite the complicated relationship between FACs and conductance, this model provides a convenient way to specify global distributions of the auroral zone conductance.